KEWIRAUSAHAAN MEMBATIK GESEK GODHONG BAGI SANTRIWATI PONDOK PESANTREN NURUL IHSAN BULULAWANG-MALANG - Alifiulahtin Utaminingsih (P3M Politeknik Negeri Malang, 2021)
Someone who has an entrepreneurial spirit is someone who acts creatively and innovatively. An entrepreneur regardless of whether due to talent or from the process of developing skills, in general, has the following characteristics: likes to try, is strong even though he fails, is confident, has good self-determination or locus of control, dares to take all risks, sees change as a challenge and chance. Santriwati is in an agricultural environment, so there are many leaves from various types of plants that can be used for the godhong batik motif. An interesting focus for community service is the godhong batik friction training because the material is quite affordable by utilizing the patterns and sap of various types of plants (leaves) that exist in our environment. The problem found is that the development of the skills of women or female students is not optimal, therefore it is necessary to develop self-capacity for santriwati Ponpes Nurul Ikhsan Malang Regency, based on creative and innovative economics through godhong batik friction skills, so as to improve life skills.